A defective nano lithium iron phosphate and its preparation method and use
By forming oxygen defects and sulfur doping in lithium iron phosphate, the problem of poor low temperature and rate performance is solved, and the low temperature cycling performance of the battery is significantly improved.
Patent Information
- Application Number
- CN202210697225.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-20
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2042-06-20
AI Technical Summary
Lithium iron phosphate (LiFePO4) has poor performance at low temperature and rate, and it is difficult for the prior art to effectively improve its low temperature cycling performance.
By forming oxygen defects in the lithium iron phosphate structure, LiFePO4 particles of the order of 50nm were synthesized by hydrothermal method, and sulfur doping was formed in the carbon material through high-temperature carbonization and vulcanization to form defective nano lithium iron phosphate.
The low-temperature cycling performance of LiFePO4 is significantly improved, and the first-circle discharge capacity and cycling performance of the battery under low temperature conditions are improved.
Smart Images

Figure CN115477294B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to defective nano lithium iron phosphate and a preparation method and application thereof, belonging to the technical field of lithium ion batteries. Background Art
[0002] As a positive electrode material, lithium iron phosphate (LiFePO4) has a stable charge and discharge platform and a high operating voltage. It has a small volume change during the cycle and exhibits good structural stability. It also has the advantages of low cost, environmental friendliness, and high safety performance. It has large-scale application prospects in the fields of new energy electric vehicles and energy storage power stations. However, the intrinsic conductivity of lithium iron phosphate is low (10 -9 ~10 -10 S / cm), the activation energy of lithium ions is only 0.3-0.5eV, and the corresponding ion diffusion coefficient is only 10-10~10-15 cm 2 / S, resulting in poor low temperature and rate performance.
[0003] In order to improve the shortcomings of lithium iron phosphate, the commonly used methods are: preparing nano-scale or special-morphology LiFePO4 particles, shortening the diffusion distance of ions and expanding the contact area with the electrolyte, thereby improving the rate performance; synthesizing carbon-coated LiFePO4 particle composites to improve electronic conductivity; metal cation doping can improve the electronic conductivity and ion diffusion coefficient of LiFePO4. Heteroatom doping such as N, S, B, etc. can change the electronic structure of carbon materials, thereby improving the carbon material's adsorption capacity for lithium ions and its own electronic conductivity, which is an effective method to improve battery performance. Summary of the invention
[0004] In order to overcome the deficiencies of the prior art, the present invention provides a defective nano lithium iron phosphate and a preparation method and use thereof, which forms oxygen defects in the LiFePO4 structure and improves the low-temperature cycle performance of LiFePO4.
[0005] The present invention is achieved through the following technical solutions:
[0006] A method for preparing defective nano lithium iron phosphate comprises the following steps: mixing and grinding lithium iron phosphate particles, a carbon source and a sulfur source to obtain a mixture, placing the obtained mixture in a tubular furnace, and subjecting the mixture to high temperature treatment under the protection of an inert gas to carbonize the carbon source, thereby forming a carbon coating on the surface of the nano lithium iron phosphate particles, and sublimating sulfur to form defects in the carbon material and the lithium iron phosphate, thereby obtaining defective nano lithium iron phosphate.
[0007] The method for preparing defective nano lithium iron phosphate specifically comprises the following steps:
[0008] (a) mixing lithium hydroxide monohydrate, phosphoric acid, ferric sulfate heptahydrate, ascorbic acid, water and ethylene glycol under magnetic stirring;
[0009] (b) transferring the reactants of step (a) into a hydrothermal kettle and reacting at a constant temperature in a forced air drying oven;
[0010] (c) After the reaction is completed, the mixture is cooled to room temperature, centrifuged and washed several times, and then transferred to a vacuum drying oven for drying to obtain nano-sized lithium iron phosphate particles;
[0011] (d) mixing and grinding the nano-sized lithium iron phosphate particles, glucose and sulfur powder to obtain a mixture;
[0012] (e) placing the mixture obtained in step (d) in a tubular furnace, and subjecting it to high temperature treatment under the protection of an inert gas to carbonize the glucose, thereby forming a carbon coating on the surface of the nano-lithium iron phosphate particles, and sublimating sulfur to form defects in the carbon material and the lithium iron phosphate, thereby obtaining a defective nano-lithium iron phosphate / carbon low-temperature positive electrode material.
[0013] The method for preparing defective nano lithium iron phosphate, in the step (a), the solution is specifically configured as follows: lithium hydroxide monohydrate is dissolved in deionized water to form solution A, phosphoric acid is dissolved in ethylene glycol to form solution B, ferrous sulfate heptahydrate and ascorbic acid are dissolved in deionized water to form solution C, solution B is first slowly added dropwise to solution A, and then solution C is added dropwise.
[0014] In the method for preparing defective nano-lithium iron phosphate, in step (a), the molar ratio of Li:Fe:P is 2-4:1:1.
[0015] In the method for preparing defective nano lithium iron phosphate, in step (b), the isothermal reaction temperature is 160-200° C. and the insulation time is 10-14 hours.
[0016] In the method for preparing defective nano lithium iron phosphate, in the step (c), the drying temperature in the vacuum drying oven is 80-100° C. and the drying time is 6-18 hours.
[0017] In the method for preparing defective nano lithium iron phosphate, in step (d), the weight ratio of nano lithium iron phosphate particles, glucose and sulfur powder is 18-22:1:1-3.
[0018] In the method for preparing defective nano lithium iron phosphate, in step (e), the calcination temperature of the tubular furnace is 600-800° C., and the calcination time is 1-3 hours.
[0019] In the step (e), the inert gas is nitrogen or argon.
[0020] The defective nano lithium iron phosphate is prepared by the method for preparing defective nano lithium iron phosphate.
[0021] The defective nano lithium iron phosphate is used for making lithium ion battery electrodes.
[0022] The beneficial effects achieved by the present invention are:
[0023] The present invention uses a hydrothermal method to synthesize 50nm LiFePO4 particles, and then uses high-temperature carbonization and sulfurization to form sulfur doping in the carbon material and defects in the LiFePO4 structure, thereby improving the low-temperature cycle performance of LiFePO4. The preparation method is simple in process and easy to operate, and can be applied to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the SEM image of the defective nano-lithium iron phosphate prepared in Example 1.
[0025] Figure 2 This is the SEM image of the defective nano-lithium iron phosphate prepared in Example 2.
[0026] Figure 3 This is the SEM image of the defective nano-lithium iron phosphate prepared in Example 3. DETAILED DESCRIPTION
[0027] The present invention is further described below. The following examples are only used to more clearly illustrate the technical solution of the present invention, and are not intended to limit the protection scope of the present invention.
[0028] Example 1
[0029] 1.2588g of lithium hydroxide monohydrate was dissolved in 10ml of deionized water under magnetic stirring to form solution A, 0.6803ml of phosphoric acid (85% concentration) was dissolved in 20ml of ethylene glycol under magnetic stirring to form solution B, 2.7802g of ferrous sulfate heptahydrate and 0.1761g of ascorbic acid were dissolved in deionized water under magnetic stirring to form solution C, solution B was slowly added to solution A with a dropper, stirred for 0.5h, then solution C was added to the above solution, and finally stirred for another 0.5h. Then the reactants were transferred to a hydrothermal kettle, kept at 160°C in a blast drying oven for 12 hours, and cooled to room temperature after the reaction. After multiple centrifugation and washing, the lithium iron phosphate positive electrode material of 50nm was obtained after being kept at 90°C in a vacuum drying oven for 12 hours. 100 mg of lithium iron phosphate cathode material, 5 mg of glucose and 10 mg of sulfur powder were mixed evenly, and calcined at 700 ° C for 2 h in a nitrogen atmosphere to obtain a defective nano lithium iron phosphate / carbon low-temperature cathode material, whose morphology is as follows: Figure 1 shown.
[0030] Example 2
[0031] 1.2588g of lithium hydroxide monohydrate was dissolved in 10ml of deionized water under magnetic stirring to form solution A, 0.6803ml of phosphoric acid (85% concentration) was dissolved in 20ml of ethylene glycol under magnetic stirring to form solution B, 2.7802g of ferrous sulfate heptahydrate and 0.1761g of ascorbic acid were dissolved in deionized water under magnetic stirring to form solution C, solution B was slowly added to solution A with a dropper, stirred for 0.5h, then solution C was added to the above solution, and finally stirred for another 0.5h. Then the reactants were transferred to a hydrothermal kettle, kept at 180°C in a blast drying oven for 12 hours, and cooled to room temperature after the reaction. After multiple centrifugation and washing, the lithium iron phosphate positive electrode material was obtained after being kept at 90°C in a vacuum drying oven for 12 hours. 100 mg of lithium iron phosphate cathode material, 5 mg of glucose and 10 mg of sulfur powder were mixed evenly, and calcined at 700 ° C for 2 h in a nitrogen atmosphere to obtain a defective nano lithium iron phosphate / carbon low-temperature cathode material, whose morphology is as follows: Figure 2 shown.
[0032] Example 3
[0033] 1.2588g of lithium hydroxide monohydrate was dissolved in 10ml of deionized water under magnetic stirring to form solution A, 0.6803ml of phosphoric acid (85% concentration) was dissolved in 20ml of ethylene glycol under magnetic stirring to form solution B, 2.7802g of ferrous sulfate heptahydrate and 0.1761g of ascorbic acid were dissolved in deionized water under magnetic stirring to form solution C, solution B was slowly added to solution A with a dropper, stirred for 0.5h, then solution C was added to the above solution, and finally stirred for another 0.5h. Then the reactants were transferred to a hydrothermal kettle, kept at 200°C in a blast drying oven for 12 hours, and cooled to room temperature after the reaction was completed. After multiple centrifugation and washing, the lithium iron phosphate positive electrode material was obtained after being kept at 90°C in a vacuum drying oven for 12 hours. 100 mg of lithium iron phosphate cathode material, 5 mg of glucose and 10 mg of sulfur powder were mixed evenly, and calcined at 700 ° C for 2 h in a nitrogen atmosphere to obtain a defective nano lithium iron phosphate / carbon low-temperature cathode material, whose morphology is as follows: Figure 3 shown.
[0034] Example 4
[0035] 1.2588g of lithium hydroxide monohydrate was dissolved in 10ml of deionized water under magnetic stirring to form solution A, 0.6803ml of phosphoric acid (85% concentration) was dissolved in 20ml of ethylene glycol under magnetic stirring to form solution B, 2.7802g of ferrous sulfate heptahydrate and 0.1761g of ascorbic acid were dissolved in deionized water under magnetic stirring to form solution C, solution B was slowly added to solution A with a dropper, stirred for 0.5h, then solution C was added to the above solution, and finally stirred for another 0.5h. Then the reactants were transferred to a hydrothermal kettle, kept at 160°C in a blast drying oven for 12 hours, and cooled to room temperature after the reaction. After multiple centrifugation and washing, a 50nm lithium iron phosphate positive electrode material was obtained after being kept at 90°C in a vacuum drying oven for 12 hours. 100 mg of lithium iron phosphate positive electrode material, 5 mg of glucose and 10 mg of sulfur powder were evenly mixed, and calcined at 600° C. for 1 h in a nitrogen atmosphere to obtain a defective nano lithium iron phosphate / carbon low-temperature positive electrode material.
[0036] Example 5
[0037] 1.2588g of lithium hydroxide monohydrate was dissolved in 10ml of deionized water under magnetic stirring to form solution A, 0.6803ml of phosphoric acid (85% concentration) was dissolved in 20ml of ethylene glycol under magnetic stirring to form solution B, 2.7802g of ferrous sulfate heptahydrate and 0.1761g of ascorbic acid were dissolved in deionized water under magnetic stirring to form solution C, solution B was slowly added to solution A with a dropper, stirred for 0.5h, then solution C was added to the above solution, and finally stirred for another 0.5h. Then the reactants were transferred to a hydrothermal kettle, kept at 160°C in a blast drying oven for 12 hours, and cooled to room temperature after the reaction. After multiple centrifugation and washing, a 50nm lithium iron phosphate positive electrode material was obtained after being kept at 90°C in a vacuum drying oven for 12 hours. 100 mg of lithium iron phosphate positive electrode material, 5 mg of glucose and 10 mg of sulfur powder were evenly mixed, and calcined at 800°C for 3 hours in a nitrogen atmosphere to obtain a defective nano lithium iron phosphate / carbon low-temperature positive electrode material.
[0038] Example 6
[0039] 1.2588g of lithium hydroxide monohydrate was dissolved in 10ml of deionized water under magnetic stirring to form solution A, 0.6803ml of phosphoric acid (85% concentration) was dissolved in 20ml of ethylene glycol under magnetic stirring to form solution B, 2.7802g of ferrous sulfate heptahydrate and 0.1761g of ascorbic acid were dissolved in deionized water under magnetic stirring to form solution C, solution B was slowly added to solution A with a dropper, stirred for 0.5h, then solution C was added to the above solution, and finally stirred for another 0.5h. Then the reactants were transferred to a hydrothermal kettle, kept at 160°C in a blast drying oven for 12 hours, and cooled to room temperature after the reaction. After multiple centrifugation and washing, the lithium iron phosphate positive electrode material of 50nm was obtained after being kept at 90°C in a vacuum drying oven for 12 hours. 100 mg of lithium iron phosphate positive electrode material and 5 mg of glucose were evenly mixed, and calcined at 700° C. for 2 h in a nitrogen atmosphere to obtain a nano lithium iron phosphate / carbon low-temperature positive electrode material.
[0040] Low temperature performance test
[0041] Battery assembly: The lithium iron phosphate / carbon positive electrode active material, acetylene black and PVDF in the embodiment are mixed evenly with a certain amount of NMP in a mass ratio of 80:10:10 to obtain a positive electrode slurry. After coating the slurry on aluminum foil, vacuum drying it at 100°C, and then rolling and punching it into 11mm discs. With metallic lithium as the counter electrode, Celgard 2300 microporous membrane as the diaphragm, and 1.0mol / L LiPF6 ethylene carbonate: dimethyl carbonate: ethyl methyl carbonate = 1:1:1 (volume ratio) solution as the electrolyte, 2032 button batteries are assembled in a glove box filled with argon. Low temperature cycle performance test was carried out using Wuhan Blue Electric Battery Test System.
[0042] Low temperature test: The battery was charged and discharged at a rate of 0.2C (1C = 170 mA / g) for two cycles at room temperature 25°C, and the charge and discharge cut-off voltage was 2.5-3.8V. The battery was then placed in a set -30°C low temperature test chamber for 10 hours, and charged and discharged at a rate of 0.2C, and the capacity and cycle performance were calculated. The results are shown in Table 1.
[0043]
[0044] From the above test results, it can be seen that the first-cycle discharge capacity and cycle performance of the defective nano lithium iron phosphate prepared in Example 1 at low temperature are higher than those of Example 2, Example 3, Example 4, Example 5 and Example 6, indicating that the use of a sulfurization strategy to construct structural defects inside lithium iron phosphate and carbon, optimize the hydrothermal temperature (comparison of Implementation 1, 2 and 3) and the back-stage sintering temperature (comparison of Implementation 1, 4 and 5) can effectively improve the low-temperature performance of lithium iron phosphate. In addition, the preparation method of the present invention is simple in process, easy to operate, and has a novel idea, and can be applied to industrial production.
[0045] It can be seen from Table 1 that although Example 6 uses the same hydrothermal reaction temperature and post-sintering process temperature as Experiment 1, sulfur powder is not used, and defects cannot be formed in the LiFePO4 structure, so the low-temperature cycle performance of LiFePO4 in Example 6 is poor.
[0046] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing defective nano lithium iron phosphate, characterized in that: The following steps are involved: The lithium iron phosphate particles, the carbon source and the sulfur source are mixed and ground to obtain a mixture, and the obtained mixture is placed in a tube furnace, and the carbon source is treated at high temperature under the protection of an inert gas to carbonize the carbon source, thereby forming a carbon coating on the surface of the nano lithium iron phosphate particles, and sulfur sublimates to form defects in the carbon material and the lithium iron phosphate, thereby obtaining defective nano lithium iron phosphate; The specific steps include: (a) mixing lithium hydroxide monohydrate, phosphoric acid, ferric sulfate heptahydrate, ascorbic acid, water and ethylene glycol under magnetic stirring; (b) transferring the reactants of step (a) into a hydrothermal kettle and reacting at a constant temperature in a forced air drying oven; (c) After the reaction is completed, the mixture is cooled to room temperature, centrifuged and washed several times, and then transferred to a vacuum drying oven for drying to obtain nano-sized lithium iron phosphate particles; (d) mixing and grinding the nano-sized lithium iron phosphate particles, glucose and sulfur powder to obtain a mixture; (e) placing the mixture obtained in step (d) in a tube furnace, and subjecting it to high temperature treatment under the protection of an inert gas to carbonize the glucose, thereby forming a carbon coating on the surface of the nano-lithium iron phosphate particles, and sublimating sulfur to form defects in the carbon material and the lithium iron phosphate, thereby obtaining a defective nano-lithium iron phosphate / carbon low-temperature positive electrode material; In the step (b), the isothermal reaction temperature is 160-200°C and the insulation time is 10-14h; In the step (e), the calcination temperature of the tubular furnace is 600-800° C., and the calcination time is 1-3 hours.
2. The method for preparing defective nano lithium iron phosphate according to claim 1, characterized in that: In the step (a), the solution is specifically configured as follows: lithium hydroxide monohydrate is dissolved in deionized water to form solution A, phosphoric acid is dissolved in ethylene glycol to form solution B, ferrous sulfate heptahydrate and ascorbic acid are dissolved in deionized water to form solution C, and solution B is first slowly added dropwise to solution A, and then solution C is added dropwise.
3. A method for preparing defective nano lithium iron phosphate according to claim 1 or 2, characterized in that: In the step (a), the molar ratio of Li:Fe:P is 2-4:1:
1.
4. The method for preparing defective nano lithium iron phosphate according to claim 1, characterized in that: In the step (c), the drying temperature in the vacuum drying oven is 80-100° C. and the drying time is 6-18 hours.
5. The method for preparing defective nano lithium iron phosphate according to claim 1, characterized in that: In the step (d), the weight ratio of the nano-sized lithium iron phosphate particles, glucose and sulfur powder is 18-22:1:1-3.
6. Defective nano lithium iron phosphate prepared according to the method for preparing defective nano lithium iron phosphate according to any one of claims 1 to 5.
7. Use of the defective nano lithium iron phosphate according to claim 6 for making lithium ion battery electrodes.
Citation Information
Patent Citations
Fluorine-doped and carbon-coated lithium iron phosphate and preparation and application thereof
CN106450223A